2020
DOI: 10.1002/marc.201900599
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Cooperativity in Polymer Blending: Toward Controlling the Thermoresponsive Behavior of Blended Block Copolymer Micelles

Abstract: Understanding, predicting, and controlling the self‐assembly behavior of stimuli‐responsive block copolymers remains a pertinent challenge. As such, the copolymer blending protocol provides an accessible methodology for obtaining a range of intermediate polymeric nanostructures simply by blending two or more block copolymers in the desired molar ratio to target specific stimuli‐responsiveness. Herein, thermoresponsive diblock copolymers are blended in various combinations to investigate whether the resultant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Thermo‐responsive behavior of diblock copolymers was also measured by the temperature‐variable UV–vis spectroscopy 29,30 . It was observed that the transmittance of copolymer solutions changed during heating.…”
Section: Resultsmentioning
confidence: 99%
“…Thermo‐responsive behavior of diblock copolymers was also measured by the temperature‐variable UV–vis spectroscopy 29,30 . It was observed that the transmittance of copolymer solutions changed during heating.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, surface adsorption of the drug to the PLGA block copolymer could result in 60-70% initial burst release (Mohammadi-Samani and Taghipour, 2015). Copolymer blending is a type of polymer blending approach in which two or more block copolymers with different characteristics, functionalities, and stimuli-responsiveness are mixed in order to form a unique polymer blend with special characteristics (Keogh et al, 2020). It has been reported that recruitment of albumin in the synthesis of block copolymers could affect drug release profile from hydrogels, while the gel consistency of the fabricated block copolymer was reduced (Perinelli et al, 2014).…”
Section: Block Copolymersmentioning
confidence: 99%
“…Among the different types of polymeric materials as drug carrier, stimuli-responsive polymers are considered attractive polymeric carriers which undergo phase transitions in response to different environmental stimuli including temperature, pH, light, and enzymes. (Keogh et al, 2020). Thermo-responsive polymers are a common type of smart or stimuli-responsive polymeric carrier that show a change in solubility at a point called critical solution temperature (CST) (Ward and Georgiou, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of the various polymers in this mixture can then be altered so that the T cp falls in the temperature range of tumors and outside of that of healthy cells. 75 Zhang et al engineered a tetrablock copolymer containing three thermoresponsive blocks: poly(polyethylene glycol methacrylate) (PPEGMA), PDMAEMA, and PNI-PAM. 30 An initial PPEGMA-PDMAEMA chain was linked to a PNIPAM block to make the LCST of the micelles formed consistent with the temperature of the body.…”
Section: ■ Moieties For Stimuli Responsivenessmentioning
confidence: 99%